Haitian Cities : Actions for Today with an Eye on Tomorrow - Lozano-Gracia, Nancy (World Bank, Washington, DC, 2018)
Today, more than half of Haiti's population calls cities and towns their home, in a major shift from the 1950s when around 90 percent of Haitians lived in the countryside. Urbanization is usually paired with economic growth, increased productivity, and higher living standards, but in Haiti it has taken a different course. Potential benefits have been overshadowed by immense challenges, all of which require immediate action. To better understand the factors that constrain the sustainable and inclusive development of Haitian cities, this Urbanization Review organizes the challenges along three dimensions of urban development namely planning, connecting, and financing. Planning reviews the challenges in supporting resilient growth to create economically vibrant, environmentally sustainable, and livable cities. Connecting focuses on the obstacles of physically linking people to jobs and businesses to markets, while financing focuses on identifying the key capital, governance, and institutional constraints that are hurdles to successful planning and connecting.